Educational Satisfaction, Academic Motivation, and Related Factors Among Nursing Students in Iran: A Cross-Sectional Study - Alireza Abdi; Mohammad Moein Mohammadi; Nargess Moradi; Zahra Khazaei (SAGE Open Nursing)
Introduction Academic motivation and educational satisfaction are crucial for nursing students’ success; however, comprehensive data on these factors remains limited. Objective This study aimed to assess academic motivation and educational satisfaction among nursing students at Kermanshah University of Medical Sciences in 2023 and explore influencing factors. Methods A descriptive-analytical study of 340 nursing students used census sampling. Data were collected via a demographic questionnaire, the Academic Motivation Scale by Vallerand, and the Motlagh Educational Satisfaction Questionnaire. Statistical analyses were conducted using SPSS version 25, with p < 0.05 considered significant. Results Participants (50% female) had a mean age of 23.12 ± 3.35 years. Over half (54.7%) reported moderate educational satisfaction, while 57.1% had very high motivation. A strong positive correlation was found between motivation and satisfaction (r = 0.58, p < 0.001), with motivation explaining 33.5% of satisfaction variance. A one-point motivation increase corresponded to a 0.24-point rise in satisfaction. Female students showed higher motivation and satisfaction (p < 0.001). Satisfaction was greater among students with homemaker mothers and those in their eighth semester, while motivation was higher for those living with family (p < 0.05). Conclusion Most students reported moderate satisfaction and high motivation, with female students scoring higher in both areas. More research is needed to uncover additional factors, and targeted interventions may improve academic outcomes and effectively support nursing students.